2018
DOI: 10.2135/cropsci2017.02.0117
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Quantitative Trait Loci for Grain Yield and Other Traits in Tropical Maize Under High and Low Soil‐Nitrogen Environments

Abstract: Low soil Nitrogen (low‐N) is one of the most important abiotic stressors responsible for significant yield losses in maize (Zea mays L.). The development and commercialization of low‐N–tolerant genotypes can contribute to improved food security in developing countries. However, selection for low‐N tolerance is difficult because it is a complex trait with strong interaction between genotypes and environments. Marker‐assisted breeding holds great promise for improving such complex traits more efficiently and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 43 publications
(46 reference statements)
4
18
1
Order By: Relevance
“…Chromosomes 1, 3 and 8 had the highest number of QTL and could be targeted for further QTL studies for GY and related secondary traits under both optimum and low-N stressed conditions. In another study [17], 13 QTL were identified under both low and high N levels. On chromosome 10, overlapping QTL were found for grain yield, ASI, and AD.…”
Section: Qtl For Gy and Secondary Traits Under Optimum And Low-n Condmentioning
confidence: 94%
“…Chromosomes 1, 3 and 8 had the highest number of QTL and could be targeted for further QTL studies for GY and related secondary traits under both optimum and low-N stressed conditions. In another study [17], 13 QTL were identified under both low and high N levels. On chromosome 10, overlapping QTL were found for grain yield, ASI, and AD.…”
Section: Qtl For Gy and Secondary Traits Under Optimum And Low-n Condmentioning
confidence: 94%
“…The identification of QTL linked to secondary traits correlated with yield performance under conditions of either Fe or Mn toxicity could further enhance the efficiency of maize breeding for tolerance to low soil pH. QTL associated with secondary traits such as days to silking, anthesis-silking interval, and stay green characteristic under stressed environments [142,143] could have the potential to be utilized as indirect molecular predictors of performance of plants exposed to Fe and Mn toxicities. Moreover, it is relevant to check whether any of the previously identified genes or QTL for Al tolerance have pleiotropic effects for tolerance to Fe and Mn toxicities.…”
Section: Application Of Molecular Tools In Breeding For Maize Toleranmentioning
confidence: 99%
“…During the past few years, the recent advances in molecular marker technologies have facilitated the construction of high-density genetic linkage maps and detection of novel QTL associated with quantitative traits in segregating populations and the characterization of the map positions in the genome of crop plants [ 26 28 ]. In maize, studies on QTL identification for complex traits have focused mainly on abiotic stresses such as drought [ 29 31 ] and low soil nitrogen [ 32 , 33 ] and good progress has been made. Also, significant advances have been made in the identification of QTLs in segregating populations under biotic stresses such as the Maize Lethal Necrosis (MLN), Southern corn rust, and Tar Spot Complex (TSC).…”
Section: Introductionmentioning
confidence: 99%